Effect of Temperature on the Formation of Quaternary Complexes of Substituted Imidazoles - Dev Das, P.; Das Manwal, Dev (Asian Journal of Chemistry, 2010)
The formation constants have been measured for the mixed ligand complexes MABL, where M = Cu(II), A = 2,2´-bipyridyl or o-phenanthroline, B = malonic acid and L = imidazole, 1-methyl-imidazole, 2-methyl-imidazole, 2-ethyl-imidazole at 25º, 35º and 45ºC. The thermodynamic parameters have also been evaluated.